2022
DOI: 10.53660/conj-810-h22
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de doses e épocas de aplicação de extrato de algas em caracteres morfológicos de cultivares de arroz no Tocantins

Abstract: As algas são fontes promissoras na elaboração de bioestimulantes, capazes de afetar o crescimento de vegetais, aumentando a eficiência de nutrientes e incrementando a resistência de plantas a estresses abióticos. Objetivou-se avaliar a biomassa e a área foliar de dois cultivares de arroz utilizando extrato de algas de água doce aplicado em diferentes estádios vegetativos. O experimento foi conduzido sob o delineamento inteiramente casualizado, com três repetições, em casa de vegetação no Campus Universitário d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to Clarke, Danila, and Von Caemmerer (2021), photosynthetically active radiation is connected to leaf area and, consequently, canopy area. Fernandes et al (2022) reported that crops with larger canopy areas are more exposed to wind and, therefore, have a higher CO 2 concentration. Therefore, considering that an adequate availability of solar radiation and CO 2 results in better crop performance, the results indicate that cherry tomato plants of the cultivar Carolina exhibit phenological characteristics for higher crop yield than those of the cultivar Yubi.…”
Section: Resultsmentioning
confidence: 99%
“…According to Clarke, Danila, and Von Caemmerer (2021), photosynthetically active radiation is connected to leaf area and, consequently, canopy area. Fernandes et al (2022) reported that crops with larger canopy areas are more exposed to wind and, therefore, have a higher CO 2 concentration. Therefore, considering that an adequate availability of solar radiation and CO 2 results in better crop performance, the results indicate that cherry tomato plants of the cultivar Carolina exhibit phenological characteristics for higher crop yield than those of the cultivar Yubi.…”
Section: Resultsmentioning
confidence: 99%